A new embedded image compression scheme using rate-distortion optimised block coding of wavelet coefficients. (2017) - Yang, Chang Mo; Chung, Kwangsue
In this paper, we propose a new embedded image compression scheme which uses rate-distortion optimised block coding (RDBC) of wavelet coefficients. Unlike conventional embedded compression schemes which use the set partition or block partition coding methods according to the magnitude of wavelet coefficients, the proposed scheme achieves rate-distortion optimisation by ordering wavelet coefficients or blocks according to their expected rate-distortion slopes. In addition, the proposed scheme uses a modified block partition method and new context models for the entropy coding. Experimental results demonstrate that the proposed scheme not only produces embedded bit-streams but also outperforms existing embedded compression schemes.